PERSEPSI AKUNTAN, PUBLIK PRIA DAN WANITA TERHADAP ISU YANG BERKAITAN DENGAN AKUNTAN PUBLIK WANITA - Yvonne Augustine S. (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
The history of women role in accounting reflected a long struggle to over-come the barriers of rigid social structures, discrimination, misconception and con-flicts between the demands of motherhood and career The accounting profession today acknowledges the issues on women in the workplace and remove remaining barriers to their mobility.This study gathers empirical evidence on the perception of professional pub-lic accountant on a number of important issues related to women in public accoun-tant. This study discusses the different perception between the gender groups of respondents toward women accountants issues.The respondents were 73 of male public accountants and 87 female public accountants. This data was analyzed using validation of Spearman correlation, Cronbach Alpha fortesting reliability, normal Kolmogorof Smimov, and Mann Whitney U-test hypothesis.The results show that there was no significant difference between the per-ception ofmale and female public accountant toward theirtreatment. However there were different perceptions in regard to opportunity, acceptance, commitment, and special accommodations.Keywords: Perception issues, gender, female public accountant